Measurement of global solar radiation on inclined surfaces of any orientation under overcast sky condition - GARG, H. P.; RAO, K. R.; PAL, R. S. (MAUSAM, 1974)
In this paper some observations of total solar radiation on sloped surfaces of different inclinations made at Roorkee under overcast sky conditions are presented along with the measuring technique. The observations indicate that the assumption of isotropy of the sky radiation under overcast sky conditions with altrostratus type of clouds is not justified. It is shown that the total radiation received by a surface of any inclination varies considerably with the orientation with respect to the sun for a given solar altitude. The ratio of total solar radiation on an inclined plane of any azimuthal orientation with respect to the sun, to that on a horizontal plane is found to be fairly independent of solar altitude. It is also observed that the albedo of the ground with green grass varies from 20 to 24 per cent.